IMPLEMENTASI PEMBELAJARAN BADMINTON LIKE GAMES DALAM UPAYA MENINGKATKAN POLA GERAK DOMINAN MEMUKUL SHUTTLECOCK DALAM AKTIVITAS PERMAINAN BULUTANGKIS: (Penelitian Tindakan Kelas Pada Siswa Kelas V SDN Binekerta Kab. Cianjur) - Hidayat, Rahmat (2016)
The aim of the research is to prove the implementation of learning badminton like games in improving dominant movement patterns strokes shuttlecock. The method used is class action research. The instrument used are observation, field note, interview and documentation. The population are the students of SDN Binakerta. The sample are 28 students of the fifth grade. The research used precentage data analysis. Base on the result of the research, it can be concluded that: 1). The implementation of learning badminton like games can improve dominant movement patterns strokes shuttlecock in the fifth grade students with the total of dominant movement patterns strokes shutlecock are 77.37%. 2). There is an effort from the teacher in developing dominant movement patterns to strike shuttlecock through learning situasion of badminton like games. 3). There is an intraction from the teacher to the student in teaching dominant movement patterns to strike shuttlecock through teaching badminton like games. Keywords: Badminton like games, dominant movement patterns, strike and badminton game.. Tujuan penelitian untuk membuktikan impelementasi pembelajaran badminton like games dalam meningkatkan pola gerak dominan memukul shuttlecock. Metode yang digunakan adalah penelitian tindakan kelas. Instrumen yang digunakan Observasi, catatan lapangan, wawancara dan dokumentasi. Populasi siswa Sekolah Dasar Negeri Binakerta. Sampel siswa kelas V berjumah 28 siswa. Penelitian ini menggunakan analisis data persentase. Berdasarkan hasil penelitian, dapat diambil kesimpulan bahwa: 1). Implementasi pembelajaran badminton like games dapat meningkatkan pola gerak dominan memukul shuttlecock siswa kelas V dengan jumlah pola gerak dominan memukul shuttlecock 77,37% 2). Adanya upaya guru dalam mengembangkan pola gerak dominan memukul shuttlecock melaui situasi pembelajaran badminton like games. 3). Adanya interaksi guru kepada siswa dalam mengajarkan pola gerak dominan memukul shuttlecock melalui pengajaran badminton like games. Kata kunci: Badminton like game, pola gerak dominan, memukul dan permainan bulutangkis.